ASPECTS OF LIFE AND HEALTH CARE COMPETENCE: THEORETICAL AND METHODOLOGICAL COMPONENTS - Chernyshov, Volodymyr (Global Prosperity, 2022)
This article provides a general overview of research on the phenomenon of life and health preservation. It is confirmed that the effectiveness of the positive impact on the health of various health and safety devices is determined not only by the quality of each of the structural elements of each of them, it is also by the adequacy of their implementation in the educational process aimed at preserving and enhancing the health of young students and teachers and the adequacy of the implementation of the objectives. Described the approach to the concept of health-improving competence as a structural unit of the education system, which acts as a quality characteristic of educational technology, determining the effectiveness of preserving the health of the subjects of the educational process in the process of achieving educational results. It is shown that the peculiarity of health-improving competence is providing the priority implementation of health monitoring in the educational process on the basis of real implementation of a humanistic approach in the system of primary education, so the concept of «health-improving competence» is general in nature. It is noted that the assessment of efficiency of educational innovation competencies implementation depends on the level of the health-improving basic framework. It has been suggested that the implementation of health and safety competence should primarily provide a comfortable environment for the development of children's potential capabilities and prevent negative influences on the health status of the stressed child. To this end, the following requirements must be taken into account: Take into account children's individual characteristics; discourage intellectual, emotional and nervous overload in the process of comprehension of the educational program; provide support for a morally and psychologically supportive climate in the classroom; Focus the teaching and learning process not only on health promotion but also on developing children's health-preserving behaviour skills, they must be taught to deal with stresses independently, and use psychological protection and health preservation tools.